The relationship between breastfeeding and infant cognitive flexibility - Goh, Fernanda Wan Yi (Nanyang Technological University, 2023)
Past research has shown that breastfeeding has positive effects on infants' cognitive development. However, fewer studies have investigated the relationship between breastfeeding and executive functions (EF), specifically cognitive flexibility (CF), and the role of touch as a potential mechanism of action. To address these gaps, a three-part study was conducted. Methods: In Part 1, the relationship between the frequency of direct latch breastfeeding and infants' CF was examined using the Child Feeding Questionnaire and the Sequential Touching Task (STT). In Parts 2 and 3, a subset of the sample was used to investigate the relationship between maternal affectionate touch (MAT) and infants' CF, as well as the combined effects of MAT and frequency of direct latch breastfeeding on CF, respectively, using the Parent-Child Interaction (PCI) task. Prediction: The study hypothesised that a greater frequency of direct latch breastfeeding would be associated with better CF performance and that the proportion of MAT would partially mediate this relationship. Results: The results showed a significant relationship between the frequency of direct latch breastfeeding and infants' CF, but no significant findings were observed for the relationships between MAT and CF. Therefore, the mediating effects of MAT on the breastfeeding and CF relationship cannot be confirmed. Discussion: The small sample size in parts 2 and 3 of the study may explain why the hypotheses were not confirmed. Future research should replicate this study with a larger sample size to increase statistical power.